(3GdbGfhf GdOhdj GdHMQj aj CHYGOg GdLOjOI (B/s - (3GdZfjej, eMeO WdYJs ((3GdEScfOQjI(B: s (3efTCI GdeYGQa(B, s, 1998)
(3GdCMcGe GdOhdjI GdNGUI HSWM GdHMQ(B- (3aj GdejGg GdOGNdjI(B- (3aj GdHMQ GdEbdjej(B- (3aj GdHMQ GdYGdj hGdeaJhM(B- (3GdefWbI GdEbJUGOjI(B- (3aj GdCMcGe GdNGUI HbGY GdHMQ(B- (3aj MeGjI GdHjFI GdHMQjIs
Keywords: (3GdbGfhf GdHMQjs; (3GdbGfhf GdOhdjs